Indução e caracterização de calos de Amburana cearensis (Allen.) A.C E Poincianella pyramidalis (Tul.) L.P.Queiroz - Costa, Evelyn Sophia Silva (2018)
The objective of this work was to establish a protocol for the induction and initiation of somatic embryogenesis of Amburana cearensis (amburana) and Poincianella Pyramidali (catingueira), establishing adequate time for callus repication and characterizing them as morphological aspects, besides performing the analysis phytochemistry of the catingueira. For the callus induction, leaf segments of amburana and cotyledonary segments for the catingueira were used as explants, all with about 1.0 cm2 of plants previously germinated in vitro. For amburana, explants were cultured in WPM medium supplemented with different concentrations of 2,4-D or picloram (0.0, 5.0, 10.0, 20.0 and 40.0 μM). for the catingueira, explants were cultured in MS / 2 medium supplemented with different associations of picloram (0.0, 2.5, 5.0, 10.0 and 20.0 μM) x BAP (0.05, 1.0 , 5.0, 10.0 μM).After 30 days of in vitro culture, the percentage of calli formed was evaluated, the growth curve of both species was determined by the fresh weight (g) of the calli. Phytochemical screening was performed to establish the phytochemical profile of catingueira extracts grown in different environments. The regression analysis showed a quadratic response for callus production for both species. After 30 days the best callus production for the amburana species was observed in the concentration of 23.83 μM of 2,4-D with 84,71% of callus formed. For the catingueira species the highest production was observed in the presence of 19,53 μM picloram + 10 μM BAP with 98.68% callus formation.Callus with friable characteristics, as well as the presence of the apigenin compound in catingueira callus suggests future work for the in vitro production of these species and the exploitation of these compounds through biotechnological techniques.